A late Maastrichtian selachian assemblage from the Peedee Formation of North Carolina, USA. - Case, Gerard R.; Cook, Todd D.; Saford, Eric M.; Shannon, Kevin R. (Vertebrate Anatomy Morphology Palaeontology, 2017)
A diverse selachian fauna was collected from the Island Creek Member of the Peedee Formation at Castle Hayne, New Hanover County, North Carolina, USA. This inner neritic assemblage consists of 23 species from eight orders, 17 families, and 20 genera and includes the new species Ptychotrygon clementsi sp. nov. The dentition of a few large macrophagous species with large palaeobiogeographical ranges is described. However, the majority of the reported specimens belong to relatively small species that are endemic to the southern regions of the Western Interior Seaway and the Atlantic and Gulf Coastal plains of North America.